South African Newspapers' Constructions of the Caster Semenya Saga through Political Cartoons. Issue 2 (3rd April 2019) - Burnett, Cora
ABSTRACT: Taking sport seriously in academic sociological writing bridged the gap between the sociology of sport and its mother discipline with a special edition in the South African Review of the Sociology in 2015. This paper addresses a global and national audience in critically reflecting on the discourses of gender, media and politics as they intersect in the construction of the Caster Semenya saga (2009–2010) through political cartoons. Reporting on female athletes in local South African newspapers mostly follows broad global trends of relative under-representation, marginalization and gender stereotyping with an exception of the Caster Semenya saga. This paper draws on the analysis of political cartoons portraying the controversies surrounding Caster Semenya during her 11-month ban and re-entry into competitive participation by July 2010. During that period, a total of 18 editorials were identified on SA Media that displayed cartoons referring to the saga under analysis. The choice of data provides visual imagery pertinent of gender ideology as it fluctuates according to dominant political discourses. These were analysed to explore layers of meanings that contributed to the hermeneutics of suspicion and constructed meanings related to prominent political, socio-cultural and gender discourses of relevance within the South African context. Descriptors (words) and images articulate to communicate powerful messages about anti-colonial sentiments, international unequal power relations that transcend sport but also impact on a nationalist agenda, the contention of fair competition and human justice within elite sport.